2018
DOI: 10.1016/j.sjbs.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Role of pollination in yield and physicochemical properties of tomatoes (Lycopersicon esculentum)

Abstract: Very little is known about pollination and its effects on the yield and physicochemical properties of flowering plants in tropical countries. Wind and insect pollinators are among our natural resources because pollination is the most important ecosystem service performed by wind and insects, and is vital to the socio-economic status of human beings. In this experiment, different pollination methods for tomato plants were examined. Self-pollination was encouraged by covering the plants with a plastic sheet. Win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 15 publications
0
21
0
4
Order By: Relevance
“…The majority of respondent farmers were of the view that pollination could be improved by promoting honey bee hives alone while they ignored the non- Apis bees. Some earlier studies, however, have shown native non- Apis bees as a better performer than honey bees for a few crops in the region (Ali et al, 2011, Bashir et al, 2018, Sajjad et al, 2009). Therefore, there was a need to train farmers on proper identification and conservation of both Apis and non- Apis native bee species.…”
Section: Discussionmentioning
confidence: 94%
“…The majority of respondent farmers were of the view that pollination could be improved by promoting honey bee hives alone while they ignored the non- Apis bees. Some earlier studies, however, have shown native non- Apis bees as a better performer than honey bees for a few crops in the region (Ali et al, 2011, Bashir et al, 2018, Sajjad et al, 2009). Therefore, there was a need to train farmers on proper identification and conservation of both Apis and non- Apis native bee species.…”
Section: Discussionmentioning
confidence: 94%
“…In tomato, Varga and Bruinsma (1986) observe that fruits with fewer seeds take longer to develop than normal fruits. In this species, a higher number of seeds per fruit results in increased fruit size (Bashir et al, 2018;Prudent et al, 2014).…”
Section: Fruit Size and Shapementioning
confidence: 99%
“…Hal ini disebabkan karakteristik dari bunga tomat yang bersifat sebagai bunga hermaprodit dengan anther harus divibrasi untuk melepaskan serbuk sari sehingga memungkinkan proses penyerbukan terjadi (Buchmann 1983). Studi menunjukkan bahwa proses vibrasasi dapat terjadi dengan bantuan serangga (Bashir et al 2018) dan angin (Vinicius-Silva et al 2017). Dengan minimnya kunjungan serangga, maka keberadaan angin menjadi faktor penting dalam produksi buah pada tanaman tomat.…”
Section: Persentase Efisiensiunclassified
“…Pada tanaman buncis, kualitas terbaik ditemukan pada kelompok buncis yang ditanam pada greenhouse sedangkan pada tomat pada kelompok tomat yang ditanam pada lahan terbuka. Hasil pada buncis sejalan dengan hasil dari Ngelenzi et al (2017) yang menunjukkan efek positif dari budidaya buncis di dalam greenhouse yang terkait dengan perlindungan terhadap faktor lingkungan dan serangan hama sedangkan hasil pada tomat sejalan dengan hasil dari Chapagain dan Wiesman ( 2004) yang melaporkan kualitas tomat yang lebih baik pada sistem budidaya di lahan terbuka yang dapat terkait dengan kesuksesan proses penyerbukan (Bashir et al 2018).…”
Section: Persentase Efisiensiunclassified